Helicobacter pylori outer membrane proteins and gastroduodenal disease. Issue 6 (1st December 2005) - Yamaoka, Y; Ojo, O; Fujimoto, S; Odenbreit, S; Haas, R; Gutierrez, O; El-Zimaity, H M T; Reddy, R; Arnqvist, A; Graham, D Y
Abstract : Background and aims: A number of Helicobacter pylori outer membrane proteins (OMPs) undergo phase variations. This study examined the relation between OMP phase variations and clinical outcome. Methods: Expression of H pylori BabA, BabB, SabA, and OipA proteins was determined by immunoblot. Multiple regression analysis was performed to determine the relation among OMP expression, clinical outcome, and mucosal histology. Results: H pylori were cultured from 200 patients (80 with gastritis, 80 with duodenal ulcer (DU), and 40 with gastric cancer). The most reliable results were obtained using cultures from single colonies of low passage number. Stability of expression with passage varied with OipA > BabA > BabB > SabA. OipA positive status was significantly associated with the presence of DU and gastric cancer, high H pylori density, and severe neutrophil infiltration. SabA positive status was associated with gastric cancer, intestinal metaplasia, and corpus atrophy, and negatively associated with DU and neutrophil infiltration. The Sydney system underestimated the prevalence of intestinal metaplasia/atrophy compared with systems using proximal and distal corpus biopsies. SabA expression dramatically decreased following exposure of H pylori to pH 5.0 for two hours. Conclusions: SabA expression frequently switched on or off, suggesting that SabA expression can rapidly respond to changing conditions in the stomach or in different regions of the stomach. SabA positive status was inversely related to the ability of the stomach to secrete acid, suggesting that its expression may be regulated by changes in acid secretion and/or in antigens expressed by the atrophic mucosa.